1976
DOI: 10.1126/science.176728
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter Regulation of Adenosine 3′,5′-Monophosphate in Clonal Nerve, Glia, and Muscle Cell Lines

Abstract: Norepinephrine increases the intracellular level of adenosine 3',5'-monophosphate (cyclic AMP) in clonal cell lines of nerve, glia, smooth muscel, and skeletal muscle. The largest response is in skeletal muscle, where the cyclic nucleotide concentration is elevated more than 500-fold. Glia and muscle cells, but not nerve cells, respond to dopamine with increased cyclic AMP accumulation. This response appears to be mediated through a beta-adrenoreceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…These findings suggest that the f-receptors present in the BC3H1 line are probably of the fl2-type (Lands et al, 1967) since they are stimulated by isoprenaline and apparently unaffected by NA up to a concentration of 10-SM. Schubert, Tarikas & La Corbiere (1976) studied the effects of NA at a concentration of 10'M in the presence of 10-3M theophylline on the cyclic AMP levels of fusing and non-fusing muscle cell lines. At these high concentrations NA has a very moderate effect on BC3H1 cells, much smaller than the stimulatory action observed in skeletal muscle myoblasts and myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the f-receptors present in the BC3H1 line are probably of the fl2-type (Lands et al, 1967) since they are stimulated by isoprenaline and apparently unaffected by NA up to a concentration of 10-SM. Schubert, Tarikas & La Corbiere (1976) studied the effects of NA at a concentration of 10'M in the presence of 10-3M theophylline on the cyclic AMP levels of fusing and non-fusing muscle cell lines. At these high concentrations NA has a very moderate effect on BC3H1 cells, much smaller than the stimulatory action observed in skeletal muscle myoblasts and myotubes.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle cells respond to 0.1 M dopamine with increases in cAMP concentrations, effects that are blocked by the ␤-adrenergic antagonist propranolol, but not by haloperidol, a dopamine receptor antagonist, or phentolamine, an ␣-adrenergic receptor antagonist (31). Carbidopa prevents the conversion of levodopa to its metabolite dopamine (6,39).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine, a metabolite of levodopa, functions through ␤-adrenergic receptors in skeletal muscle (31), although it is unclear whether dopamine at the concentration (ϳ1 ng/g) at which it is found in skeletal muscle in the absence of exogenous levodopa treatment (11) has a true physiological function. Muscle cells respond to 0.1 M dopamine with increases in cAMP concentrations, effects that are blocked by the ␤-adrenergic antagonist propranolol, but not by haloperidol, a dopamine receptor antagonist, or phentolamine, an ␣-adrenergic receptor antagonist (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in the level of CAMP was observed [5] after fusion to myotubules. The large increase in intracellular CAMP levels subsequent to the noradrenergic stimulation of L6 cells [4] indicates the presence of a large population of /3-adrenergic receptor sites on the cell surface. Indeed, direct binding studies with 1251-labeled +hydroxybenzyl-pindolol ([ 12'1] +HYP) confirmed the presence of a large number of f3-adrenergic receptor sites on L6P cells [7].…”
Section: Introductionmentioning
confidence: 99%